Study of gene polymorphisms as predictors of treatment efficacy and toxicity in patients with indolent non‐hodgkin lymphomas and mantle cell lymphoma receiving bendamustine and rituximab. (11th September 2018) - Cencini, Emanuele; Sicuranza, Anna; Fabbri, Alberto; Ferrigno, Ilaria; Rigacci, Luigi; Cox, Maria C.; Raspadori, Donatella; Bocchia, Monica
Summary: Bendamustine is used in combination with rituximab (BR) to treat indolent non‐Hodgkin lymphomas (iNHL) and mantle cell lymphoma (MCL). The variability in treatment efficacy and toxicity could be related to single nucleotide polymorphisms (SNPs) in immune response genes. We would like to show a correlation between SNPs and treatment outcome in iNHL and MCL patients receiving BR. We investigated some SNPs that had already been associated with NHL outcome. Samples were genotyped for the IL2 (rs2069762), IL10 (rs1800890, rs10494879), VEGFA (rs3025039), IL8 (rs4073), CFH (rs1065489) and MTHFR (rs1801131) SNPs by allelic discrimination assays. We enrolled 70 patients that received rituximab 375 mg/m 2 and bendamustine 90 mg/m 2 every 28 days, both as first‐line treatment and ≥ second‐line regimens. Overall response rate was 97·1% (complete response [CR] rate 73·9%). Treatment toxicity included grade 3–4 neutropenia (24/70 patients), infections (21/70 patients; 1/70 grade 3), skin rash (26/70 patients; 2/70 grade 3). After a median follow‐up of 24 months we did find any correlation between the analysed SNPs, CR rate and PFS. However, we demonstrated an association between the SNP in IL2 (rs2069762) and the onset of skin rash ( P  = 0·0001). Our study suggests a role for cytokine SNPs in bendamustine‐related toxicity, which could represent a promising research field.